2008
DOI: 10.1002/vnl.20161
|View full text |Cite
|
Sign up to set email alerts
|

Polymer plasticization using supercritical carbon dioxide

Abstract: The plasticizing effect of supercritical CO2 (scCO2) during the extrusion of polymers was investigated. A modified extrusion system was used to demonstrate the viscosity‐reducing effect of scCO2 together with a capability to produce foam‐free extrudate with selected polymers, including poly(vinyl chloride). Samples of extrudate and materials prepared off‐line by using a pressure vessel were characterized by thermal, mechanical, and X‐ray techniques. After gas diffusion from the polymer, there was no long‐term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This is because of the plasticizing effect of the CO 2 injected during extrusion. It is well known that CO 2 is able to serve as an effective plasticizer during melt processing [30][31][32][33]. Once CO 2 is injected and blended into the melt, the viscosity, shear stress, and shear heating of the melt flow can be significantly reduced during melt processing, and thus the molecular weight and melt strength can be better preserved after processing.…”
Section: Resultsmentioning
confidence: 99%
“…This is because of the plasticizing effect of the CO 2 injected during extrusion. It is well known that CO 2 is able to serve as an effective plasticizer during melt processing [30][31][32][33]. Once CO 2 is injected and blended into the melt, the viscosity, shear stress, and shear heating of the melt flow can be significantly reduced during melt processing, and thus the molecular weight and melt strength can be better preserved after processing.…”
Section: Resultsmentioning
confidence: 99%
“…In general, it has been shown that CO 2 acts as a molecular lubricant when it is absorbed into a polymer, increasing segmental and chain mobility and also increasing interchain distance [29]. Due to this local increase in mobility, the glass transition temperature is dramatically reduced and the polymer flows more easily.…”
Section: Introductionmentioning
confidence: 99%